Build Loyalty with Islamic Relationship Marketing and Trust Through Satisfaction - Saddam Husein; Anas Hidayat; Tamamudin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This study examines and explains how loyalty is built with Islamic relationship marketing and trust through customer satisfaction. The success of a company in getting satisfied customers will have an impact on customer loyalty. Although relationship marketing research is a popular topic, research on relationship marketing from an Islamic perspective is very limited. Relationship marketing from an Islamic perspective is interesting because it is very relevant to be practicedin today's business development. The quantitative approach used in this study, the data collection method through questionnaires with non-probability sampling techniques, the number of respondents was 76, the data analysis technique used in this study was Path Analysis. The results showed that there was a relationship between Islamic relationship marketing and trust which had a direct effect on customer satisfaction. Islamic relationship marketing and trust directly affect loyalty, and consumer satisfaction has a direct effect on loyalty. Consumer satisfaction can play a role as a mediating variable between Islamic relationship marketing and trust on loyalty.